Recent Rise of Climate Change and Islamic Perspectives: A Research Review - Dr. Farhat Naseem Alvi,; Dr. Abdul Manan Cheema, (MEI, 2023)
Recent rise of climate change is a global challenge. It has become the biggest threat to the natural ecosystem of Earth, human life, and future generations. The latest climate reports of international panel on climate (IPCC) indicate that climate variations have sensitized the entire world. Therefore, it is essential to take preventive measures to reduce impact of climate change for protection of living beings and future generations on Earth. Power plants, fossil fuels, greenhouse gases, transportation, industrial revolution, non-renewable energy resources, and deforestation are main reasons of climate changes. Deforestation has augmented imbalance, disorder, global warming, climate change, air pollution and other ecological issues at local, regional and global level. Forests are considered lungs of the ecosystem. Religious ecological principles can play an effective role to eradicate ecological and climate changes. Islam is an eco-friendly religion. Islam provides complete guidance in every walk of life. This research study provides a comprehensive analysis of how Islam guides people in addressing and mitigating the global challenge of climate change. Islamic ecological precautions can play an exquisite role in minimizing impact of climate change on humane life. Global climate changes have affected Pakistan in form of unseasonal heavy rains, extreme flooding and drought. The main objective of this article is to provide an overview of climate change impact and its solutions in the light of Islamic perspectives.